Assessment and Practice of Information and Research Literacy Skills among Students in Indian Higher Education Institutions - Sohail, Md; Sharma, Asha (DESIDOC Journal of Library & Information Technology, 2023)
The study presented and focused on the process and implementation of the information and research literacy program, the level of awareness among students and research scholars, and their potential after receiving information and research literacy training. The purpose of this study is to learn more about users' information and research literacy skills when it comes to various information sources and services. The essential component of information literacy provided students with a significant amount of insight into the practical instructional methods they could use to use the information sources without difficulty. The aim of this study is to assess the level of information and research literacy among students in Indian higher education institutions and to identify areas for improvement. The study found that while students have basic knowledge of information and research literacy, they struggle with more advanced research skills such as finding, evaluating, and synthesizing information. To separate the content, a list of 33 topics was used, covering the majority of topics to measure the awareness of information and research literacy skills and how to overcome their improper implementation among students and research scholars. The study highlights the need for institutions to prioritize the development of these skills through targeted training and practice opportunities.